Agorafolly : Outside / Inside. - Ruyters, Marc; Vandenberghe, Joan; La centrale électrique, Bruxelles; Brussel (Brussels : Europalia International, 2007)
Shurelov, Venelin ; Nys, Sophie ; Walther, Sebastian ; Verschaere, Fabien ; Camilleri, Austin ; Vetik, Helene ; Valk, Veronika ; Cerevka, Radovan ; Oliveira, Rodrigo ; Velderman, Wouter Klein ; Sandlund, Fia-Stina ; Couta, Melita ; et al.
Outside: 27 pleinen, Brussel, 13.10.2007-09.12.2007 / Inside: La centrale électrique, Brussel, 13.10.2007-13.01.2008
kunstcatalogus